Evaluation of Ovicidal and Larvicidal Activities of Methylene Chloride-Methanol Extract of Annona Senegalensis (Annonaceae) Stem Bark on Heligmosomoides Bakeri (Nematoda, Heligmosomatidae) (Global Journal of Science Frontier Research, 2014)
Abstract not found
Keywords: heligmosomoides bakeri; Annona senegalensis; ovicidal; larvicidal; anthelminthic